Triggers for freezing of gait in individuals with Parkinson’s disease: a systematic review - Conde, Carolina I.; Lang, Charlotte; Baumann, Christian R.; Easthope, Chris A.; Taylor, William R.; Ravi, Deepak K. (Frontiers in Neurology, 2023)
Background Freezing of Gait (FOG) is a motor symptom frequently observed in advanced Parkinson’s disease. However, due to its paroxysmal nature and diverse presentation, assessing FOG in a clinical setting can be challenging. Before FOG can be fully investigated, it is critical that a reliable experimental setting is established in which FOG can be evoked in a standardized manner, but the efficacy of various gait tasks and triggers for eliciting FOG remains unclear. Objectives This study aimed to conduct a systematic review of the existing literature and evaluate the available evidence for the relationship between specific motor tasks, triggers, and FOG episodes in individuals with Parkinson’s disease (PwPD). Methods We conducted a literature search on four online databases (PubMed, Web of Science, EMBASE, and Cochrane Library) using the keywords “Parkinson’s disease,” “Freezing of Gait”, “triggers” and “tasks”. A total of 128 articles met the inclusion criteria and were included in our analysis. Results The review found that a wide range of gait tasks were employed in studies assessing FOG among PD patients. However, three tasks (turning, dual tasking, and straight walking) emerged as the most frequently used. Turning (28%) appears to be the most effective trigger for eliciting FOG in PwPD, followed by walking through a doorway (14%) and dual tasking (10%). Conclusion This review thereby supports the utilisation of turning, especially a 360-degree turn, as a reliable trigger for FOG in PwPD. This finding could be beneficial to clinicians conducting clinical evaluations and researchers aiming to assess FOG in a laboratory environment.